2014
DOI: 10.1159/000356219
|View full text |Cite
|
Sign up to set email alerts
|

Improved Frontoparietal White Matter Integrity in Overweight Children Is Associated with Attendance at an After-School Exercise Program

Abstract: Aerobic fitness is associated with white matter integrity (WMI) in adults as measured by diffusion tensor imaging (DTI). This study examined the effect of an 8-month exercise intervention on WMI in children. Participants were 18 sedentary, overweight (BMI ≥85th percentile) 8- to 11-year-old children (94% Black), randomly assigned to either an aerobic exercise (n = 10) or sedentary attention control group (n = 8). Each group was offered an instructor-led after-school program every school day for approximately 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 36 publications
11
93
2
2
Order By: Relevance
“…These results are consistent with Krafft et al 25 who observed that attendance in an 8-month exercise program was positively associated with improved white matter integrity among a group of sedentary and overweight (BMI $ 85th percentile) 8-to 11-yearolds (94% African American). However, the findings from the current study provide further support for the importance of PA program attendance for cognitive benefit among a large heterogeneous sample of children with varying weight status.…”
Section: Figuresupporting
confidence: 91%
“…These results are consistent with Krafft et al 25 who observed that attendance in an 8-month exercise program was positively associated with improved white matter integrity among a group of sedentary and overweight (BMI $ 85th percentile) 8-to 11-yearolds (94% African American). However, the findings from the current study provide further support for the importance of PA program attendance for cognitive benefit among a large heterogeneous sample of children with varying weight status.…”
Section: Figuresupporting
confidence: 91%
“…Krafft et al (98) report on data from 43 participants and Krafft et al (99) report on data from 18 participants. Results in both studies indicated that there were no significant interactions of group with time, suggesting that PA participation did not influence changes in cognitive performance as assessed using the CAS from pretest to posttest.…”
Section: Resultsmentioning
confidence: 99%
“…Further evidence of the effects of PA on brain structure stems from two randomized controlled pilot studies (99, 138). These studies were conducted using subsamples from the SMART study that employed diffusion tensor imaging (DTI), which is an MRI technique that affords in vivo characterization of white matter microstructure based on the properties of diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…Aerobic fitness has been correlated with better performance on tasks assessing cognition and memory as well as the volumes of specific brain structures, such as the basal ganglia [5] and hippocampus [6], with higher-fit children demonstrating larger volumes and superior performance. Other research has imaged white matter tracts connecting prefrontal cortex with other brain regions, and found that children who were more fit [7] or received daily PA had greater structural integrity following the intervention [8], with intervention compliance (i.e., attendance) related to increased white matter integrity [9]. …”
Section: Physical Activitymentioning
confidence: 99%